Currency Hedging for a Dutch Investor: The Case of Pension Funds and Insurers (2015)
This paper analyzes the risk reduction effectiveness of currency hedging international portfolios from the perspective of an average Dutch pension fund and insurer during the period 1999-2004. Several portfolios and approaches to hedging are analyzed. Passive hedging seems to be efficient in reducing the volatility of a foreign bond portfolio whereas the risk reduction achieved for a foreign equity portfolio is not significant. The case of mixed (bonds and equities) portfolios and hedging is also analyzed. No significant risk reduction (at the same level of returns as that of an unhedged portfolio) was attained using a static hedging approach and portfolio optimization under short sale constraints. Using a selective (dynamic) hedging approach based on the forward premium, showed similar results; the volatility of an unhedged and hedged portfolio was virtually the same. Nevertheless, this selective hedging strategy had a positive impact improving the hedged portfolio returns.